ALTERNATIF PERENCANAAN KOMPOSISI CAMPURAN BETON DENGAN GABUNGAN BAHAN TAMBAH KIMIA TIPE F DAN D AGAR WAKTU BUKA ACUAN DIPERCEPAT - Juandra Hartono; Masrianto Masrianto; Indira L. Widuri; Bhima Dhanardono; Hinawan T. Santoso (Jurnal Jalan-Jembatan, 2022)
The demand for an acceleration of project completion time is often an obstacle, especially in structural work which is a critical path. The length of time for concrete curing and formwork dismantling sometimes obstructs the progress of the project. The time required for casting, concrete curing and unloading of formwork in a long span bridge construction project is ± 14 days with a record that there are no obstacles in the field. Based on these problems, researchers are trying to provide an alternative solution through a compressive strength test with a variant of the concrete quality and the curing time using chemical additives type F and type D. The study aims to find the minimum concrete compressive strength, the curing time, and the effects of adding a chemical additive that refers to General Specifications Standard 2018 (70% of the designed concrete compressive strength). The variant of the concrete quality is 40 MPa, 50 Mpa, and 60 Mpa while the variant of the curing time is 1,2,3,7, and 28 days. Based on the study, the minimum concrete compressive strength for each concrete quality is 28,58 MPa, 36,85 MPa, and 46,25 MPa. The curing time needed for fc’ 40 MPa and fc’ 50 Mpa is 2 days while for fc’ 60 MPa is 3 days. The use of chemical additives also has an impact on increasing compressive strength. The maximum compressive strength value of 28 days is found in the variation of f'c 60 Mpa of 62.20 Mpa with additive content of type F dan D of 0.6% and 0,15% of the cement weight. Optimum compressive strength is achieved when the curing process is done using the soaking method. Key words: critical path, formwork, chemical additives, compressive strength, soaking method.